2009
DOI: 10.1038/ajg.2009.188
|View full text |Cite
|
Sign up to set email alerts
|

Between Celiac Disease and Irritable Bowel Syndrome: The “No Man's Land” of Gluten Sensitivity

Abstract: The repertoire of gastrointestinal (GI) symptoms is finite; however, the etiologies and mechanisms underlying symptom generation and perception are diverse and, in many cases, unknown. This review examines the clinical and experimental evidence exploring the putative relationship between gluten sensitivity (GS) and the generation of GI symptoms. It explores the hypothesis that, in a proportion of patients, GS causes functional bowel disorder (FBD)-like symptoms. We propose a model for investigating and underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
154
0
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(173 citation statements)
references
References 95 publications
3
154
0
12
Order By: Relevance
“…As 34 out of 160 patients (22%) showed gluten hypersensitivity, it would be interesting to place these subjects in the complex category of gluten sensitivity. 30 Previous works have demonstrated that gliadin can induce an increased intestinal permeability and innate immune cell activation. However, these studies NOTE.…”
Section: Discussionmentioning
confidence: 99%
“…As 34 out of 160 patients (22%) showed gluten hypersensitivity, it would be interesting to place these subjects in the complex category of gluten sensitivity. 30 Previous works have demonstrated that gliadin can induce an increased intestinal permeability and innate immune cell activation. However, these studies NOTE.…”
Section: Discussionmentioning
confidence: 99%
“…Falsepositive biopsies may also result from overinterpretation of specimens or poor specimen orientation. Of 19 patients, 9 with negative serology had minimal lesions; these patients, despite HLA compatibility and response to GFD, would not be celiac according to Biagi et al [27], but would be considered gluten-sensitive patients, according toVerdu et al [28].…”
Section: Discussionmentioning
confidence: 99%
“…This is the clinical history, in particular, of the patients with IBS-like clinical manifestations [ 2 ]. In this respect, the possible relationship between IBS and gluten-sensitivity has been underlined very recently [ 13 ], although the pathogenesis of this condition still remains to be clarified and probably different subgroups of patients are wrongly included under an unique " gluten-sensitivity category " [ 10 ]. The major clinical problem in ascertaining whether patients with IBS really suffer from GS or FH is the lack of accurate diagnostic assays.…”
Section: Discussionmentioning
confidence: 99%